2015
DOI: 10.1515/cttr-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biomarkers of Exposure and Subjective Effects When Smokers Switch to Dual Use of Cigarettes and Either Snus or a Dissolvable Tobacco Product: A Summary of Three Clinical Studies

Abstract: SUMMARYA series of ambulatory clinical studies were conducted to evaluate changes in biomarkers of tobacco exposure and subjective product ratings when adult smokers switched to dual use of cigarettes with Camel Strips (Strips), Camel Sticks (Sticks), or Camel (SNUS). In all studies, subjects smoked ad libitum for one week (baseline). In incremental stages over three subsequent weeks, subjects were instructed to reduce cigarettes per day (CPD) by at least 75% and include use of one type of smokeless tobacco pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Excretion of o -Tol in smokers (CC) on Day 3 was in the range of 91.0–260.7 (mean: 150.2) ng/24 h (Table ). This is overall in good agreement with a series of other studies. , NU of any tobacco/nicotine products in our study showed o -Tol excretion rates in the range of 30.4–77.2 (mean: 60.2) ng/24 h (Table ). Agreement with reported o -Tol excretions in nonsmokers is acceptable. , Urinary o -Tol levels in NU confirm the relatively high and diffuse background exposure of the general population to this aromatic amine. , In some earlier studies, significantly higher o -Tol concentrations in urine (μg/L range) were reported in nonoccupationally exposed smokers and nonsmokers, with no significant differences observed between the two groups. Possibly, there were issues with the specificity of the analytical methods applied in these studies.…”
Section: Discussionsupporting
confidence: 93%
“…Excretion of o -Tol in smokers (CC) on Day 3 was in the range of 91.0–260.7 (mean: 150.2) ng/24 h (Table ). This is overall in good agreement with a series of other studies. , NU of any tobacco/nicotine products in our study showed o -Tol excretion rates in the range of 30.4–77.2 (mean: 60.2) ng/24 h (Table ). Agreement with reported o -Tol excretions in nonsmokers is acceptable. , Urinary o -Tol levels in NU confirm the relatively high and diffuse background exposure of the general population to this aromatic amine. , In some earlier studies, significantly higher o -Tol concentrations in urine (μg/L range) were reported in nonoccupationally exposed smokers and nonsmokers, with no significant differences observed between the two groups. Possibly, there were issues with the specificity of the analytical methods applied in these studies.…”
Section: Discussionsupporting
confidence: 93%
“…Whether the reductions in exposure to toxicants such as those observed in this study may have the potential to reduce risks for chronic, smoking-caused diseases for long-term e-cigarette users who have partially or completely discontinued cigarette smoking warrants further investigation. It has been previously shown that for those Swedish smokers who completely switch from cigarettes to a noncombustible form of tobacco (snus, which delivers nicotine without smoke) there appears to be an association with lower relative risks for major smoking-related disease, including cancer (Round et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary biomarker analysis was performed by ABF GmbH (Munich, Germany), and plasma nicotine and cotinine analysis was performed by Celerion, Inc. (Lincoln, NE). Methods are generally as described in Theophilus et al 34 and Round et al, 35 with one exception. The calculation of total nicotine equivalents includes unconjugated nicotine, unconjugated cotinine, unconjugated trans-3′-hydroxycotinine, nicotine-N-glucuronide, cotinine-N-glucuronide, trans -3′-hydroxycotinine-O-glucuronide, cotinine-N-oxide, nicotine-N-oxide, norcotinine, nornicotine, and 4-hydroxy-4-(3-pyridyl)-butanoic acid 36 …”
Section: Methodsmentioning
confidence: 99%